Can Energetic Terahertz Pulses Initiate Surface Catalytic Reactions on the Picosecond Time Scale? - Bruce D. Patterson; Bill Pedrini; Jeroen A. van Bokhoven; Hans C. Sigg; Regula Gehrig; Izabela Czekaj; Clemens Ruchert; Carlo Vicario; Christoph P. Hauri; AnastasijaIchsanow; Jacinto Sa; Rafael Abela (CHIMIA, 2011)
In preparation for picosecond pump-probe experiments at the SwissFELX-ray laser facility, the feasibility of collectively initiating surface chemical reactions using energetic pulses of terahertz radiation is being tested.